2003
DOI: 10.1002/job.220
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and team outcomes: the moderating effects of outcome interdependence and group longevity and the mediating effect of reflexivity

Abstract: Reflexivity—the extent to which teams reflect upon and modify their functioning—has been identified as a possible key factor in the effectiveness of work teams. We examined the extent to which team composition affected team process (i.e., reflexivity) and in turn team outcomes (i.e., satisfaction, commitment, and performance). The results of diversity research thus far have been inconclusive in terms of positive or negative effects of team composition on team process and outcomes. In the current research, grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
321
1
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(347 citation statements)
references
References 65 publications
8
321
1
7
Order By: Relevance
“…The findings revealed that that the impact on team performance in short term teams was positive(mean score values :combined mean =3.23, age =3.1, gender=3.3, ethnic=3.3).This was in accordance with the study proposition 3a which was also supported by the interview results .In the long run, however divisions based on relations oriented diversity may become more debilitating for the team performance (Schippers et al, 2003).As predicted the long term impact of relation diversity factors was negative(mean score values :combined mean =2.63, age =2.7, gender=2.5, ethnic=2.7) .This along with the interview results supported the hypothesis 3b proposed in this study.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The findings revealed that that the impact on team performance in short term teams was positive(mean score values :combined mean =3.23, age =3.1, gender=3.3, ethnic=3.3).This was in accordance with the study proposition 3a which was also supported by the interview results .In the long run, however divisions based on relations oriented diversity may become more debilitating for the team performance (Schippers et al, 2003).As predicted the long term impact of relation diversity factors was negative(mean score values :combined mean =2.63, age =2.7, gender=2.5, ethnic=2.7) .This along with the interview results supported the hypothesis 3b proposed in this study.…”
Section: Resultssupporting
confidence: 84%
“…The same study also noted that in more tenured diverse teams, team members had more conflicts due to relational differences and the motivation to resolve differences through interaction and communication phased out over the time. On the other hand, in the short term, most of the team members in highly diverse teams communicated their differences to accomplish the team's task (Schippers et al, 2003;Watson et al, 1998). Based on this view, the present study test the following proposition …”
Section: Time and Team Tenurementioning
confidence: 99%
“…Edmondson (1996Edmondson ( , 1999 showed that team leaders giving guidance, encouragement, and support to the team members by coaching and considerate leadership influence psychological safety in teams, which in turn promotes team learning behaviors. Schippers et al (2003) showed that inspirational, charismatic, and intellectual stimulation (all indicators of transformational leadership) (e.g., Bass, 1985) stimulate reflexivity in teams by creating a shared vision. Srivastava, Bartol, and Locke (2006) showed that empowering leadership, conceptualized in five personfocused leadership dimensions (i.e., leading by example, participative decision making, coaching, informing, and showing concern for the team), is positively related to knowledge sharing in management teams.…”
Section: Leadership and Team Learning Behaviorsmentioning
confidence: 99%
“…Research has shown that team learning is related to various leadership behaviors, such as, transformational leadership (Schippers et al, 2003), empowering team leadership (Srivastava, Bartol, & Locke, 2006; Burke, Stagl, Klein, Goodwin, Salas, & Halpin, 2006), and team leader coaching (Edmondson, 2003). Based on these results it can be argued that the project manager, as leader of a project team, has a prominent role in stimulating team learning behaviors, involving members in decision making, clarifying team goals, providing bridges to outside parties via the leader's 5 status in the organization (Sarin & McDermott, 2003), and challenging and facilitating the processes of dialogue and experimentation by de-emphasizing power differences and by facilitating a psychologically safe context (see, e.g., Burke et al, 2006; Edmondson, 1999 Edmondson, , 2003 Costanzo & Tzoumpa, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, attitudinal and behavioral changes have been used as indicators for the presence or absence of reflection (e.g., Kember & Leung, 2000;Leung & Kember, 2003;Peltier et al, 2005). In addition, individual and group level outcomes of reflection were separately tested in terms of educational performance, decision making or problem solving (e.g., Mol et al, 2005;Carter & West, 1998;Schippers et al, 2003;Frame, 2013). In general, most previous studies were based on selfreport measures, in which the meaning of reflection was (implicitly) assumed to be clear to respondents, though never explicated.…”
Section: Reflection and Reflective Questioningmentioning
confidence: 99%